2006
DOI: 10.1152/ajpheart.01045.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential autocrine modulation of atrial and ventricular potassium currents and of oxidative stress in diabetic rats

Abstract: . Differential autocrine modulation of atrial and ventricular potassium currents and of oxidative stress in diabetic rats. Am J Physiol Heart Circ Physiol 290: H1879 -H1888, 2006. First published December 9, 2005 doi:10.1152/ajpheart.01045.2005The autocrine modulation of cardiac K ϩ currents was compared in ventricular and atrial cells (V and A cells, respectively) from Type 1 diabetic rats. K ϩ currents were measured by using whole cell voltage clamp. ANG II was measured by ELISA and immunofluorescent labeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…In rats with type 1 diabetes mellitus, for example, the angiotensin II level is elevated in ventricular cells, but not in atrial cells. 41 Combining local regulation with induction of abnormal mRNA processing might contribute to a phenotype that varies according to clinical state.…”
Section: Intrinsic Modifiersmentioning
confidence: 99%
“…In rats with type 1 diabetes mellitus, for example, the angiotensin II level is elevated in ventricular cells, but not in atrial cells. 41 Combining local regulation with induction of abnormal mRNA processing might contribute to a phenotype that varies according to clinical state.…”
Section: Intrinsic Modifiersmentioning
confidence: 99%
“…However, diabetes has been well documented to cause significant K + ion channel abnormalities. [35][36][37] An intriguing possibility is suggested by the observations of Shander et al, 31 who observed a hyperpolarizing shift in the voltage-dependence of steady-state inactivation of I Na in response to application of lysophosphatidylcholine (LPC). It has been demonstrated that activation of calcium-independent phospholipase A 2 in the STZdiabetic rat heart leads to accumulation of lysophopholipids, 19 thus suggesting a possible mechanism underlying alterations of the voltage-dependence of I Na gating.…”
Section: Impact On Future Experimental Workmentioning
confidence: 99%
“…Atrial and ventricular cardiomyocytes present different cell morphologies, structures, energy metabolisms and calcium regulations [12,13]. Additionally, oxidative stresses and pathophysiological responses are significantly different between left and right atrium or between ventricles and atria [14][15][16]. Hence, it is critical to investigate the effects of diabetes on PPARs expression in different cardiac regions.…”
Section: Introductionmentioning
confidence: 99%